Carbon–Nitrogen Bond Cleavage by a Thorium‐NHC‐bpy Complex. Issue 44 (4th October 2016) - Garner, Mary E.; Hohloch, Stephan; Maron, Laurent; Arnold, John
Abstract: Actinide complexes demonstrate unparalleled reactivity towards small molecules. However, utilizing these powerful transformations in a predictable and deliberate manner remains challenging. Therefore, developing actinide systems that not only perform noteworthy chemistry but also demonstrate controllable reactivity is a key goal. We describe a bis(NHC)borate thorium‐bpy complex (1 ) that is capable of reductively cleaving the R−NC bond in a series of organic isocyanides. In contrast to most actinide‐mediated bond activations, the dealkylation event mediated by1 is remarkably general and yields very well‐defined products that assist in mechanistic elucidation. Synthesis of the rearranged but‐3‐enyl product from the reaction of1 and cyclopropylmethyl isocyanide supports the notion of a radical‐based mechanism. Abstract : Thor's hammer : A bis(NHC)borate thorium‐bpy complex (1 ) is described that reductively cleaves the R−NC bond in a series of organic isocyanides. In contrast to most actinide‐mediated bond activations, the dealkylation event mediated by1 is remarkably general and yields very well‐defined products. The production of the rearranged but‐3‐enyl product from the reaction of1 and cyclopropylmethyl isocyanide supports the notion of a radical‐based mechanism.